Human Security and Democratic Administrations in Nigeria’s Fourth Republic - Ogundare, Yemi Daniel (Hasanuddin University, 2024)
This paper examines democratic administrations and human security in Nigeria’s fourth republic. The fourth republic was the first republic in Nigeria's history that witnessed a long democratic transition which is still in continuation. The wide assumption is that democratic institution has strong leverage for human security. But from Nigeria's perspective, it is not certain that democracy has promoted the human security of the citizens’ livelihood. The objective of the paper is to assess the impact of democratic administrations on the livelihood of the citizens. The theory of this research was the sustainable development theory. The research methodology is a triangulation method descriptive and explorative in Nature. The findings revealed that democracy in Nigeria had not been able to solve the human security dimensional aspect of livelihood security. One of the focal recommendations is a strong political institution that can produce an effective rule of law and accountability government to the people.